1998
DOI: 10.1007/s004280050160
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural pathology of the alveolar type II pneumocytes of human donor lungs

Abstract: Alveolar type II pneumocytes (PII) were studied in 12 human donor lungs perfused with modified Euro-Collins solution during single-lung transplantation (SLTx). While one lung was transplanted, the contralateral donor lung (cDL) was fixed at the time of SLTx for examination by electron microscopy, stereology, and microanalysis. Three groups were then formed: group A (n = 7), cDL without contusions, uneventful early postoperative course; group B (n = 3), cDL with conclusions, uneventful early postoperative cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Photomicrographs were recorded by a digital camera (DP-25; Olympus, Tokyo, Japan) attached to a microscope (BX-51; Olympus) at 40-and 100-fold magnification using Olympus cell^A software. For mucus assessment, systematic uniform random samples of lung tissue were taken according to standard methods (17) including the orientator technique (18). The surface area of mucin-containing goblet cells (S gc ) per total surface area of airway epithelial basal membrane (S ep ) and the volume of PASstained epithelial mucin (V mucin ) per S ep were determined using a computer-assisted stereology tool box (newCAST, Visiopharm, Hoersholm, Denmark) (19,20), according to the following formulas: S ge /S ep = + Igc / + Iep and V mucin /S ep = LP 3 (+P mucin /2) 3 + Iep , where + Igc is the sum of intersections of test lines with goblet cells, + Iep is the sum of all intersections of test lines with the epithelial basal membrane, +P mucin is the sum of all points hitting mucin, and LP is the test-line length at final magnification.…”
Section: Lung Histologymentioning
confidence: 99%
“…Photomicrographs were recorded by a digital camera (DP-25; Olympus, Tokyo, Japan) attached to a microscope (BX-51; Olympus) at 40-and 100-fold magnification using Olympus cell^A software. For mucus assessment, systematic uniform random samples of lung tissue were taken according to standard methods (17) including the orientator technique (18). The surface area of mucin-containing goblet cells (S gc ) per total surface area of airway epithelial basal membrane (S ep ) and the volume of PASstained epithelial mucin (V mucin ) per S ep were determined using a computer-assisted stereology tool box (newCAST, Visiopharm, Hoersholm, Denmark) (19,20), according to the following formulas: S ge /S ep = + Igc / + Iep and V mucin /S ep = LP 3 (+P mucin /2) 3 + Iep , where + Igc is the sum of intersections of test lines with goblet cells, + Iep is the sum of all intersections of test lines with the epithelial basal membrane, +P mucin is the sum of all points hitting mucin, and LP is the test-line length at final magnification.…”
Section: Lung Histologymentioning
confidence: 99%
“…The perfusion fixation was performed for 15 min (11)(12)(13)(14)(15)(16)(17)(18)(19)) (median [min-max]), which encompassed a closed loop perfusion time with the fixative solution of 9 min (7)(8)(9)(10)(11). Perfusion pressure (determined as inflow pressure minus a left atrial pressure of 0, i.e., open to atmosphere) was 12.5 mm Hg [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and subsequently 20 mm Hg (14-33) during perfusion with the fixative.…”
Section: Perfusion Fixationmentioning
confidence: 99%
“…Perfusion pressure (determined as inflow pressure minus a left atrial pressure of 0, i.e., open to atmosphere) was 12.5 mm Hg [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and subsequently 20 mm Hg (14-33) during perfusion with the fixative. Continuous airway pressure applied to the lungs was 12.5 mbar (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)). An illustration of the pressure tracings from animal 14 during the fixation procedure is given in Figure 3.…”
Section: Perfusion Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that bronchial artery revascularization (BAR) can improve graft function from the early post-operative period by mitigating ischemia-reperfusion injury. [3][4][5] We previously demonstrated increased marker enzyme activities for type II pneumocytes and pulmonary endothelium in standard lung transplantation compared with BAR. 6 To date, there is no information with regard to tissue oxygenation of the severed bronchial and lung tissue during and after lung transplantation.…”
mentioning
confidence: 98%